L’indépendance cubaine au miroir du cinéma : enjeux idéologiques, esthétiques et historiographiques - Julie Amiot (Caravelle)
This article broaches the subject of national independence in Cuban films, in order to reveal that films produced within the framework of the commemorations of this event in 1968 stand out through their quantity as well as through their quality. Yet this formal proliferation mustn’t leave out that these projects were clearly inscribed in a very tense discursive framework, installed at the beginning of the Revolution by means of speeches and legislative texts strictly framing the film production, from the material point of view as well as through the contents of works. Therefore, the analysis of speeches accompanying the films enables to show that the putting forward of their formal creativity –real– has lead to save thinking about the ideological conformism of their content.